2017
DOI: 10.1016/j.jalz.2017.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Exploring APOE genotype effects on Alzheimer's disease risk and amyloid β burden in individuals with subjective cognitive decline: The FundacioACE Healthy Brain Initiative (FACEHBI) study baseline results

Abstract: The FACEHBI sample presents APOE ε4 enrichment, suggesting that a pool of AD patients is nested in our sample. Cerebral amyloid levels are partially explained by the APOE allele dosage, suggesting that other genetic or epigenetic factors are involved in this AD endophenotype.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 46 publications
1
22
0
Order By: Relevance
“…Because the ApoE ε4 allele, the major genetic risk factor for AD, 39 is also known to be correlated with SMCs, 21 , 22 ApoE genotyping was performed according to methods described previously. 40 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because the ApoE ε4 allele, the major genetic risk factor for AD, 39 is also known to be correlated with SMCs, 21 , 22 ApoE genotyping was performed according to methods described previously. 40 …”
Section: Methodsmentioning
confidence: 99%
“… 18 , 19 Studies can be categorized according to the baseline cognitive status of the subjects (CN, 5 , 12 MCI, 12 and non-dementia) 12 , 18 , 19 or their final disease status (AD, 5 , 12 dementia). 18 , 19 Many studies have also identified the confounding factors of SMCs including depression, 5 , 12 age, 5 , 12 gender, 5 , 12 level of education, 5 , 12 , 20 vascular burden, 10 ApoE ε4 status, 12 , 21 , 22 and executive dysfunction. 7 …”
Section: Introductionmentioning
confidence: 99%
“…Notably, amyloid deposition in subjects with SCD is also affected by other risk factors for dementia due to AD, such as the ApoE ɛ4 genotype and age. Individuals with SCD may present higher allelic frequencies of ApoE ɛ4, and cerebral amyloid levels might be partially predicted by the ApoE ɛ4 level [ 42 ]. In another study of individuals with SCD from the Alzheimer’s Disease Neuroimaging Initiative (ADNI) database, ApoE ɛ4 carriers with SCD showed higher levels of amyloid accumulation than noncarriers.…”
Section: Positron Emission Tomographymentioning
confidence: 99%
“… McCluskey.et al (2018) [ 32 ] MAC-Q 1 binary question 18 F-florbetaben PET Cross-sectional All: n=112(69.2, 2.5) Self-reported confusion predicted higher global amyloid burden and regional amyloid in the prefrontal, posterior cingulate, precuneus and the lateral temporal. Moreno–Grau et al (2018) [ 42 ] Cognitive complaints 18 F-florbetaben PET 18 F-florbetapir PET Cross-sectional ADNI_NC: n=182(73.4±6.3) ADNI_SMC: n=103(72.2±5.6) ADNI_EMCI: n=303(71.3±7.4) ADNI_LMCI: n=157(72.2±7.5) ADNI_AD: n=144(74.4±8.1) FACEHBI_SCD: n=200(65.8±7.1) ADNI_NC: n=182(73.4±6.3) Higher ApoE ɛ4 carrier in SCD and ApoE ɛ4 dosage explained 9% and 11% cerebral amyloid variation. Perrotin et al (2017) [ 23 ] Composite of 26 questions 18 F-florbetapir PET MRI Cross-sectional Controls: n=35(65.6±8.6) SCDcommunity: n=35(70.8±7.5) SCDclinic: n=28(67.6±7.7) Both groups with high self-reported difficulties has higher amyloid deposition Perrotin et al (2012) [ 25 ] 2 questions PiB-PET MRI Cross-sectional High PiB uptake: n=11(75.73±6.05) Low PiB uptake: n=28(71.89±5.45) Correlation between memory self-reports and regional PiB uptake in right medial prefrontal, anterior cingulate, right precuneus and posterior cingulate.…”
Section: Positron Emission Tomographymentioning
confidence: 99%
“…MCI due to AD, also known as amnestic MCI, is when a patient’s cognitive capacity is below the level appropriate to their age, gender, and education level, but the cognitive decline has not reached dementia level. SCD is a cognitively-normal individual with self-reported cognitive impairment, suggestive of a prodromal AD phase [8, 9].…”
Section: Introductionmentioning
confidence: 99%